Characterization of Agricultural Households Socioeconomic on Javanese and To Pekurehua Ethnic in Central Sulawesi Province - Rustam Abd Rauf; Lien Damayanti; Erny; Aulia Rakhman; Chitra A. Salingkat; Shintami R. Malik; Hardiyanti Sultan; Mukhlis (Jurnal Penelitian Pendidikan IPA, 2025)
Central Sulawesi is categorized as a food and nutrition insecure area, due to drought, narrow land ownership, high population migration, and the absence of a non-agricultural economic sector. This study aims to analyze socio-economic factors household, namely Javanese and To Pekurehua (Napu valley). This research was conducted in Central Sulawesi Province in 2 sub-districts namely Napu Valley and Java. Sampling using simple random sampling method. Determination of the number of samples using the Slovin formula consisting of 120 respondents. Data collection using in-depth interviews and direct observation. Quantitative data processing by tabulating. Data analysis was conducted by: (1) Descriptive to answer socioeconomic characteristics; (2) Quantitative to answer meal frequency and measure food consumption. For household food security level, Food Expenditure Share calculation was used. The results showed that: The results showed: (1) Household food security is categorized as food resilient, with a share of food expenditure of less than 60%, namely 55.62% for to pekurehua (Lembah napu) and 56.68% for Java; (2) Social and economic factors that influence the ability to access adequate and nutritious food are household income, equitable distribution of food and adequate infrastructure. to pekurehua and Java ethnicities have similar characteristics in meeting food needs.